FLUORESCENT LABELED ANTI-EGFR ANTIBODY FOR IDENTIFICATION OF REGIONAL AND DISTANT METASTASIS IN A PRECLINICAL XENOGRAFT MODEL - Gleysteen, John P. (Head Neck, 2008)
BACKGROUND: Detection of regional and distant metastatic disease has significant implications for patient management. Fluorescent imaging may be a useful technique for metastasis detection and removal. METHODS: Anti–epidermal growth factor receptor antibody (cetuximab) and isotype-matched control antibody (immunoglobulin G [IgG]) were labeled with a near-infrared fluorophore (Cy5.5), then systemically administered to mice with tumors resulting from either intraoral or intravenous injections of head and neck squamous cell carcinoma. Mice were sacrificed before undergoing fluorescent stereomicroscopy to assess pulmonary or cervical lymph node metastasis. Fluorescent areas were serially excised until wound bed demonstrated negative fluorescence. RESULTS: Mice bearing pulmonary metastases displayed diffuse background after IgG–Cy5.5 injection, but demonstrated a speckled fluorescent pattern across lung surface following cetuximab–Cy5.5 injection. Mice bearing cervical metastases demonstrated clear fluorescence of primary tongue tumor and bilateral cervical nodes. Fluorescence correlated with histopathology. CONCLUSION: These data suggest that cetuximab–Cy5.5 may have clinical utility in the detection and guided the removal of regional and distant micrometastasis.